Festival motivation and loyalty factors - Kitterlin, Miranda (2024)
Every year hundreds of festivals and host communities around the world face increased competition from both each other and from other entertainment options available to the consumer. It is imperative that festival organizers understand tourist motivations for attending festivals in order to conduct effective festival planning and achieve a more productive festival marketing position and marketing strategy. The purpose of this study is twofold: First, this study attempted to investigate whether festivalscape factors impact attendees’ motivation and loyalty behavior. Additionally, this study attempted to examine whether festivalscape factors are influenced by different types of attendees. Practical implications for festival organizers and marketers include the importance of the customization of operational and marketing strategies depending on their target market (local versus non-local). Academic contributions of this study pertain to the theoretical foundations by validating the impact of festivalscape factors in tourism marketing.